Capital Structure Memediasi Antara Growth Opportunity Dan Leverage Terhadap Firm Value Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Nahda Nabilah; Saiful Anwar (UMSurabaya Publishing, 2022)
ABSTRACT The purpose of this study is to examine the effect of growth opportunity and leverage on firm value with capital structure as an intervening variable. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used purposive sampling with 20 sample companies. Data were analyzed using WARP PLS 6.0. The results of this study are that growth opportunity has a significant effect on firm value, and leverage has an impact. Still, it is not substantial on strong value, capital structure has an effect but is not marked on firm value, growth opportunity has an effect but is not significant. On the capital structure, leverage has a significant impact on capital structure; growth opportunity has an important but not significant impact on firm value with capital structure as an intervening variable, leverage has no significant effect on firm value with capital structure as an intervening variable.Keywords : Growth Opportunity; Leverage; Firm Value; Capital StructureCorrespondence to : nahdanabilah@ymail.com ABSTRAKTujuan studi ini guna menguji pengaruh growth opportunity dan leverage terhadap firm value dengan capital structure sebagai variabel intervening. Populasi dalam studi ini yaitu perusahaan manufaktur yang tercatat di Bursa Efek Indonesia tahun 2016-2020. Teknik pengambilan sampel menggunakan purposive sampling dengan 20 perusahaan sampel. Data dianalisis menggunakan WARP PLS 6.0. Hasil penelitian ini adalah Growth opportunity berpengaruh signifikan pada firm value, Leverage berpengaruh namun tidak signifikan pada firm value, Capital structure berpengaruh namun tidak signifikan pada firm value, Growth opportunity berpengaruh namun tidak signifikan pada capital structure, Leverage berpengaruh signifikan pada capital structure, Growth opportunity berpengaruh namun tidak signifikan pada firm value dengan capital structure sebagai variabel intervening, Leverage berpengaruh namun tidak signfikan pada firm value dengan capital structure sebagai variabel intervening.Kata Kunci : Growth Opportunity; Leverage; Firm Value; Capital Structure